Preparation method of three-layer ceramic composite membrane

By pre-preparing the Al2O3 film layer on the macroporous support and preparing the TiO2 film layer on its surface to form a three-layer ceramic composite film, the problem of easy cracking of the TiO2 film layer during heat treatment is solved, and the pure water flux of the ceramic film is improved, meeting the needs of large-scale applications.

CN119819138AActive Publication Date: 2025-04-15NANJING TECH UNIV

Patent Information

Application Number
CN202510115720.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-15
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

During the preparation of TiO2 ceramic membrane, the large pore size of the carrier leads to uneven stress of the membrane layer, which is prone to cracking during the heat treatment process, affecting the integrity and performance of the membrane, and also leads to a decrease in the flux of pure water, making it difficult to meet the needs of large-scale applications.

Method used

The Al2O3 film layer was prepared in advance on the macroporous support, and the TiO2 film layer was continued to be prepared on the surface of the Al2O3 film layer to form a three-layer ceramic composite film. After applying the TiO2 sol film liquid, freeze-drying and calcining is adopted by a vacuum freeze-dryer to reduce the changes in the membrane structure caused by high temperature and avoid cracking of the membrane layer.

Benefits of technology

It effectively avoids the cracking problem of TiO2 film layer, and at the same time improves the pure water flux of the ceramic film, meeting the needs of large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819138A_ABST
    Figure CN119819138A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a ceramic membrane, in particular to a preparation method of a three-layer ceramic composite membrane. According to the invention, the Al2O3 film layer is prepared on the macroporous carrier by using the boehmite sol film preparation liquid in advance, and the TiO2 film layer is prepared on the Al2O3 film layer, so that cracking of the TiO2 film layer can be avoided. And after the TiO2 sol membrane preparation liquid is coated, the three-layer ceramic composite membrane is subjected to freeze drying by adopting a vacuum freeze dryer and then is calcined, so that the prepared three-layer ceramic composite membrane has the advantage of large flux while membrane layer cracking is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a ceramic membrane, in particular to a method for preparing a three-layer ceramic composite membrane. Background Art

[0002] Compared with organic membranes, inorganic membranes have outstanding features such as good thermal stability, mechanical strength, and high temperature resistance. Ceramic membranes are typical inorganic membrane materials and are widely used in harsh production working environments such as biomedicine, energy and chemical industries.

[0003] Among them, TiO2 materials are ideal materials for preparing ceramic membranes due to their good chemical stability, low cost, high hydrophilicity, etc., and the preparation research of TiO2 membranes has also received extensive attention. Sol-gel method is an important process for preparing ceramic membrane materials. This process can prepare a separation layer of high-performance ceramic membranes with uniform pore size, narrow pore size distribution, and reliable quality. The sol-gel method has the advantages of low production cost, simple process, and easy adjustment of composition in the process of preparing TiO2 ceramic membranes. It is considered to be the preferred method for industrial production of TiO2 ceramic membranes among many methods.

[0004] In the process of preparing TiO2 ceramic membranes, in order to ensure the flux, a large-pore carrier is often used. However, the large pore size of the carrier causes uneven stress in the TiO2 film layer, which causes cracking of the film layer during the heat treatment process and further affects the integrity and performance of the membrane. In order to solve the above problems, the inventors tried to prepare an Al2O3 film layer before preparing the TiO2 film on the surface of the carrier, and then continue to prepare the TiO2 film layer on the surface of the Al2O3 film layer to form a three-layer ceramic composite membrane. This method can solve the problem of film cracking very well, but what comes with it is that the three-layer ceramic membrane causes a decrease in pure water flux, which is difficult to meet the needs of large-scale applications. Therefore, how to improve the pure water flux of the ceramic membrane while solving the problem of film cracking during the heat treatment of the TiO2 ceramic membrane is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0005] In view of the above problems, the present invention uses boehmite sol film-making liquid to prepare Al2O3 film layer on a macroporous carrier in advance, and prepares TiO2 film layer on the Al2O3 film layer, which can avoid the cracking of TiO2 film layer. After applying TiO2 sol film-making liquid, a vacuum freeze dryer is used for freeze drying and then calcination, so that the prepared three-layer ceramic composite membrane can avoid cracking of the film layer while having the advantage of large flux.

[0006] The present invention provides a three-layer ceramic composite membrane, which comprises a ceramic carrier, an Al2O3 film layer and a TiO2 film layer connected in sequence, wherein the average pore size of the ceramic carrier is 100-500nm, and the average pore size of the three-layer ceramic composite membrane is 2-5nm.

[0007] The present invention also provides a method for preparing the above three-layer ceramic composite membrane, which comprises the following steps: Step 1: prepare boehmite sol and TiO2 sol film-forming solutions respectively; Step 2: applying the boehmite sol on the surface of the carrier, drying it, and calcining it to form an Al2O3 film layer; Step 3: Continue to apply TiO2 sol film-making liquid on the surface of the Al2O3 film layer, and place it in a vacuum freeze dryer, freeze it at a temperature below minus 50°C for 2-5 hours, vacuum dry it for 5-20 hours, and then bake it to form the three-layer ceramic composite film.

[0008] Preferably, the preparation steps of the boehmite sol in step 1 are: dissolving aluminum isopropoxide in water and mixing evenly, then adding a nitric acid solution at a certain dilution ratio, and finally adding a polyvinyl alcohol solution and anhydrous ethanol to obtain the boehmite sol.

[0009] Preferably, the mass ratio of aluminum isopropoxide, nitric acid, polyvinyl alcohol, water and anhydrous ethanol in the boehmite sol is 1:0.05-5:0.1-0.5:10-50:10-50.

[0010] Preferably, in step 1, the preparation steps of the TiO2 sol film-forming solution are: Tetrabutyl titanate and concentrated nitric acid are added to an anhydrous ethanol solution, mixed and then slowly added dropwise to a solution containing deionized water, concentrated nitric acid and ethanol, and after continuous stirring, a hydroxypropyl cellulose aqueous solution is added to obtain a TiO2 sol film-forming solution.

[0011] Preferably, the molar ratio of Ti(OC4H9)4:HNO3:C2H5OH:H2O in the TiO2 sol film-forming solution is 1:0.25-1:2-5:3-10, and the mass fraction of hydroxypropyl cellulose in the TiO2 film-forming solution is 0.1-0.5%.

[0012] Preferably, the carrier in step 2 is a ceramic carrier with a pore size of 100-500 nm.

[0013] Preferably, the drying in step 2 is drying at room temperature for 5-20 hours, the calcination temperature is 600-1200° C., and the calcination time is 1-6 hours.

[0014] Preferably, the coating of the boehmite sol in step 2 and the coating of the TiO2 sol film-forming solution in step 3 are both performed by immersion-pulling method, with an immersion-pulling rate of 2-10 mm / s and an immersion time of 5-120 s.

[0015] Preferably, the freezing temperature in step 3 is (-80) - (-55°C).

[0016] Preferably, the calcination temperature in step 3 is 200-400° C., the calcination time is 2-5 h, and the heating and cooling rate is 0.5-2° C. / min.

[0017] Compared with the prior art, the present invention has the following advantages: Firstly, the present invention innovatively prepares a layer of Al2O3 film between the macroporous carrier and the TiO2 film layer in advance, thereby ensuring the uniform stress of the TiO2 film layer, thereby solving the problem of easy cracking of the TiO2 film layer prepared by the sol-gel method on the macroporous carrier.

[0018] Secondly, while solving the problem of easy cracking of TiO2 membranes prepared with macroporous carriers, the present invention adopts a vacuum freeze dryer to freeze-dry and then calcine after coating the TiO2 sol membrane-making liquid, which can reduce the changes in the membrane structure caused by high temperature during the drying process, thereby preparing an ultra-thin TiO2 membrane structure. Compared with the prior art, the membrane thickness of the present invention does not exceed 5μm, and the average pore size of the three-layer ceramic composite membrane is 2-5nm, which significantly improves the water flux of the ceramic membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The surface / cross-section SEM images of the coatings prepared by coating three groups of TiO2 sol film-forming solutions with different acid-titanium molar ratios on the transition layer, wherein the acid-titanium ratios of a, b, and c are 1, 0.75, and 0.5, respectively; Figure 2 The particle size distribution diagram of TiO2 sol under four groups of acid-titanium ratios; Figure 3 This is the main position distribution diagram of aluminum and titanium elements in the composite film layer; Figure 4 The retention data of the coatings prepared by two carriers with two average pore sizes under different aging methods, where L is vacuum freeze drying and H is constant temperature and humidity. DETAILED DESCRIPTION

[0020] Example 1 Example 1 The three-layer ceramic composite membrane is prepared by the following steps: Add aluminum isopropoxide to pure water heated to 85°C, stir and mix them evenly, then slowly add nitric acid solution, and continue stirring until the solution becomes a light blue clear solution. The above clear solution is stirred and mixed with polyvinyl alcohol solution and anhydrous ethanol to prepare a white boehmite sol. The ratio of aluminum isopropoxide: nitric acid: polyvinyl alcohol: deionized water: anhydrous ethanol in the solution is 1:: 0.1: 0.23: 26.1: 23.8, where the density of nitric acid solution is 0.01g / ml, and the mass fraction of polyvinyl alcohol solution is 6.5%. Select a carrier with an average pore size of 400nm and place it in the film-making solution at a rate of 5mm / s using an immersion puller for coating. The immersion time is 60s, and coating is done once. The coated carrier is placed at room temperature for 12h and then calcined at 900℃ for 3h to obtain an aluminum oxide film layer, where the heating and cooling rates during the calcination process are all 1min / ℃.

[0021] According to the molar ratio of Ti(OC4H9)4:HNO3:C2H5OH:H2O of 1:0.5:3.7:5, tetrabutyl titanate and concentrated nitric acid were added to anhydrous ethanol solution, mixed and slowly added to a solution containing deionized water, concentrated nitric acid and ethanol, and stirred for 2 hours to prepare a light blue clear TiO2 sol, and 38.75g of 0.3% hydroxypropyl cellulose aqueous solution was added as an organic additive to form a stable and uniform TiO2 sol film-making liquid. The surface of the aluminum oxide film layer was coated with an immersion puller at a rate of 5mm / s, and coated 4 times at room temperature, with an immersion time of 15s each time.

[0022] After coating, it was placed in a cold trap of a vacuum freeze dryer at -70°C for 3 hours and then dried in a vacuum environment for 12 hours. Finally, it was placed in a muffle furnace and calcined in an air atmosphere. It was heated to 350°C at a heating rate of 1°C / min and kept warm for 3 hours. Then it was cooled to room temperature at a rate of 1°C / min to obtain a uniform and complete three-layer ceramic composite film.

[0023] Example 2 The difference from Example 1 is that in Example 2, the TiO2 sol film-forming liquid is applied twice on the surface of the Al2O3 film layer.

[0024] Example 3 The difference from Example 1 is that a carrier with an average pore size of 200 nm is selected.

[0025] Comparative Example 1 The difference from Example 1 is that after the TiO2 sol film-forming liquid is coated, it is aged in a constant temperature and humidity chamber at a temperature of 60°C and a relative humidity of 70% for 12 hours.

[0026] Comparative Example 2 The difference from Comparative Example 1 is that the molar ratio of tetrabutyl titanate: concentrated nitric acid: anhydrous ethanol: deionized water in the TiO2 sol film-forming liquid is 1:1:3.7:5.

[0027] Comparative Example 3 The difference from Comparative Example 1 is that the molar ratio of tetrabutyl titanate: concentrated nitric acid: anhydrous ethanol: deionized water in the TiO2 sol film-forming liquid is 1:0.75:3.7:5.

[0028] Comparative Example 4 The difference from Implementation 3 is that the TiO2 sol film-forming liquid is applied twice.

[0029] Characterization The samples of the above examples and comparative examples were subjected to average pore size measurement and pure water flux measurement, and the pressures during the interception test and pure water flux test were 0.2 MPa and 0.1 MPa, respectively. The results are as follows: Table 1 Performance results of ceramic composite membranes prepared in different embodiments and comparative examples in addition, Figure 1 The surface / cross-section SEM images of the coatings prepared by coating the transition layer with three groups of TiO2 sol film-forming solutions with different acid-titanium molar ratios. Figure 1 It can be seen that the TiO2 sol film-forming liquid under the three groups of acid-titanium ratios can be successfully attached. Figure 2 The TiO2 sol particle size under different acid-titanium ratios shows that as the acid-titanium ratio decreases, the sol particle size increases, and the coating effect of the membrane liquid is better. EDX element characterization of the cross section of the calcined composite ceramic membrane found that (such as Figure 3 ), the titanium element is mainly concentrated on the outermost side, and because the TiO2 sol particle size is small, there will be a very small amount of titanium element in the inner alumina transition layer and ceramic carrier. Figure 4 It can be seen that in Example 2, when the acid-titanium ratio is 0.5 and the number of coatings is 2, the TiO2 sol coated on the surface of the ceramic alumina support with an average pore size of 400 nm is aged by freeze-drying procedure to prepare a membrane layer for interception test. When the interception rate of dextran is 90%, the corresponding dextran molecular weight is 12521 Da. According to the Stokes equation The pore radius can be calculated, so d=2r. The average pore size of the membrane layer is 5.06nm, and the average pore size of the coating is the largest. The corresponding pure water flux reaches the highest 25.3L / m 2 ·h -1 bar -1Combined with the above characterization data, it can be seen that the TiO2 membrane layer prepared by aging the membrane-forming solution coated on the surface of the support with an average pore size of 400 nm (when the TiO2 sol membrane-forming solution is coated on the surface of the Al2O3 membrane layer twice) using a vacuum freeze-drying procedure has the highest pure water permeation flux.

Claims

1. A three-layer ceramic composite membrane, characterized in that: The three-layer ceramic composite membrane comprises a ceramic carrier, an Al2O3 membrane layer and a TiO2 membrane layer connected in sequence, the average pore size of the ceramic carrier is 100-500nm, and the average pore size of the three-layer ceramic composite membrane is 2-5nm.

2. A method for preparing a three-layer ceramic composite membrane according to claim 1, characterized in that: The following steps are involved: Step 1: prepare boehmite sol and TiO2 sol film-making solutions respectively; Step 2: applying the boehmite sol on the surface of the carrier, drying it, and calcining it to form an Al2O3 film layer; Step 3: Continue to apply TiO2 sol film-making liquid on the surface of the Al2O3 film layer, and place it in a vacuum freeze dryer, freeze it at a temperature below minus 50°C for 2-5 hours, vacuum dry it for 5-20 hours, and then bake it to form the three-layer ceramic composite film.

3. The preparation method according to claim 2, characterized in that: The preparation steps of the boehmite sol in step 1 are: Aluminum isopropoxide is dissolved in water and mixed evenly, then a nitric acid solution at a certain dilution ratio is added, and finally a polyvinyl alcohol solution and anhydrous ethanol are added to obtain a boehmite sol.

4. The preparation method according to claim 3, characterized in that: The mass ratio of aluminum isopropoxide, nitric acid, polyvinyl alcohol, water and anhydrous ethanol in the boehmite sol is 1:0.05-5:0.1-0.5:10-50:10-50.

5. The preparation method according to claim 2, characterized in that: In step 1, the preparation steps of TiO2 sol film-making solution are as follows: Tetrabutyl titanate and concentrated nitric acid are added to an anhydrous ethanol solution, mixed and then slowly added dropwise to a solution containing deionized water, concentrated nitric acid and ethanol, and after continuous stirring, a hydroxypropyl cellulose aqueous solution is added to obtain a TiO2 sol film-forming solution.

6. The preparation method according to claim 5, characterized in that: The molar ratio of Ti(OC4H9)4:HNO3:C2H5OH:H2O in the TiO2 sol film-forming solution is 1:0.25-1:2-5:3-10, and the mass fraction of hydroxypropyl cellulose in the TiO2 film-forming solution is 0.1-0.5%.

7. The preparation method according to claim 1, characterized in that: The drying in step 2 is drying at room temperature for 5-20 hours, the calcination temperature is 600-1200° C., and the calcination time is 1-6 hours.

8. The preparation method according to claim 1, characterized in that: The coating of the boehmite sol in step 2 and the coating of the TiO2 sol film-forming solution in step 3 are both coated by the immersion-pulling method, with an immersion-pulling rate of 2-10 mm / s and an immersion time of 5-120 s.

9. The preparation method according to claim 1, characterized in that: The freezing temperature in step 3 is (-80) - (-55°C).

10. The preparation method according to claim 1, characterized in that: The calcination temperature in step 3 is 200-400° C., the calcination time is 2-5 h, and the heating and cooling rate is 0.5-2° C. / min.

Citation Information

Patent Citations

  • Gradient porous ceramics film and method for preparing the same

    CN101182233A

  • Preparation method of high-flux and high-precision ceramic ultrafiltration membrane for oil removal and iron removal of high-temperature condensed water

    CN105561803A

  • Al2O3-TiO2 gradient porous structure ceramic ultrafiltration membrane and preparation method thereof

    CN110681263A

  • Preparation method of composite ceramic membrane

    CN111499361A

  • A method and reactor for catalytic partial oxidation of hydrocarbons

    WO2017216420A1

Cited By

  • Method for preparing crack-free ceramic composite ultrafiltration membrane based on freeze drying technology and sol-gel method

    CN121588643A